2015
DOI: 10.1186/s13569-014-0020-9
|View full text |Cite
|
Sign up to set email alerts
|

Ganglioside GD2 expression is maintained upon recurrence in patients with osteosarcoma

Abstract: BackgroundOsteosarcoma is the most common primary malignant bone tumor in children and young adults. Ganglioside GD2 has been previously found on the cell surface in various tumor types, including osteosarcomas.FindingsIn this study, forty-nine additional osteosarcoma samples from 14 individual patients were assessed for GD2 expression via immunohistochemistry, of which 47 samples were found to express GD2. In matched samples from patients, GD2 expression seen at initial biopsy was found to persist in 100% of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 10 publications
2
43
0
1
Order By: Relevance
“…Despite this, we were encouraged by preliminary results suggesting clinical benefit of a first generation GD2-specific CAR in patients with neuroblastoma and sought to assess the efficacy of a costimulation-endowed CAR against pediatric sarcomas. We assessed GD2 expression on three common histologies and confirmed that it is expressed on essentially all osteosarcomas, with a sizable fraction of primary and metastatic tumors expressing a high level (22,39,40). Our results confirm those from Kailayangiri et al demonstrating GD2 on Ewing sarcoma cell lines, although we did not observe significant expression of GD2 on Ewing sarcoma tissues (23).…”
Section: Discussionmentioning
confidence: 75%
“…Despite this, we were encouraged by preliminary results suggesting clinical benefit of a first generation GD2-specific CAR in patients with neuroblastoma and sought to assess the efficacy of a costimulation-endowed CAR against pediatric sarcomas. We assessed GD2 expression on three common histologies and confirmed that it is expressed on essentially all osteosarcomas, with a sizable fraction of primary and metastatic tumors expressing a high level (22,39,40). Our results confirm those from Kailayangiri et al demonstrating GD2 on Ewing sarcoma cell lines, although we did not observe significant expression of GD2 on Ewing sarcoma tissues (23).…”
Section: Discussionmentioning
confidence: 75%
“…Ten years later, a phase I clinical trial revealed that a human+mouse chimeric monoclonal antibody (mAb) ch 14.18 directed against disialoganglioside (GD2) appeared to be clinically safe and effective with no specific toxicity after repeated administration [129]. An immunohistochemical study demonstrated that all the osteosarcoma tumours analysed were positive for GD2 in a series composed of 44 patients [130], and persisted upon recurrence [131]. '# " $%, GD2 was suspected of enhancing the aggressiveness of the osteosarcoma [132].…”
Section: Disialoganglioside (Gd2)mentioning
confidence: 99%
“…Nearly all osteosarcomas tumors expressed GD2 by immunohistochemistry in a recent investigation;[25] subsequent analysis showed that in relapsed patients, GD2 expression was universally maintained upon recurrence. [26] Several trials utilizing varied forms of anti-GD2 therapy are currently open (NCT02173093; NCT00743496; NCT02107963; NCT02502786). Clinical trials are currently in development for the use of denosumab, glembatumumab vedotin, and dinutuximab for the treatment of recurrent and refractory osteosarcoma.…”
Section: Introductionmentioning
confidence: 99%